Pengaruh Profitabilitas, Likuiditas Leverage, Assets Growth, Ukuran Perusahaan dan Kepemilikan Institusional Terhadap Kebijakan Dividen Pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Uqba, Luthfia Aulia; Lela Hindasah (Politeknik Negeri Ambon, 2025)
Dividend distributions among non-financial companies listed on the Indonesia Stock Exchange (IDX) often exhibit inconsistency, highlighting a disparity between market expectations and actual performance. Variability in the Dividend Payout Ratio (DPR) can diminish a company’s appeal in the capital market, weaken investor confidence, and discourage investment interest. This research aims to examine the effect of profitability, liquidity, leverage, asset growth, company size, and institutional ownership on dividend policy in non-financial companies listed on the IDX during the period from 2019 to 2023. Using a sample of 625 observations, the study employs multiple linear regression analysis to determine the key factors that influence dividend decisions, with STATA 17 as the primary analytical tool. The results show that profitability and asset growth have a significant negative impact on dividend policy, while liquidity, leverage, company size, and institutional ownership do not have a significant effect